2015
DOI: 10.1371/journal.pone.0134209
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Innate COPD Alveolar Macrophage Responses and Toll-Like Receptor-9 Polymorphisms

Abstract: BackgroundDysfunctional innate responses of alveolar macrophages to nontypeable Haemophilus influenzae, Moraxella catarrhalis and Streptococcus pneumoniae contribute to morbidity in chronic obstructive pulmonary disease (COPD). Our earlier studies discovered impaired COPD alveolar macrophage responses to Toll-like receptor (TLR) ligands of nontypeable H. influenzae and provide rationale for further evaluation of TLR signaling. While the role of TLR single nucleotide polymorphisms is increasingly recognized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
18
0
2
Order By: Relevance
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of a previous study reported that the TLR9 gene causes an intracellular receptor signal cascade, and thus evokes nuclear transcription factors resulting in the production of pro-and anti-inflammatory cytokines (Hemmi et al, 2000). The authors of previous studies have reported that TLR9 gene polymorphisms are associated with the development of several inflammatory diseases (Bharti et al, 2014;Berenson et al, 2015;Trejo-de la O et al, 2015;Wen et al, 2015;Wujcicka et al, 2015). Bharti et al (2014) conducted a study in a Chinese population and assessed the association between TLR9 polymorphisms and pulmonary tuberculosis; they found that the TLR9 rs187084 polymorphism was associated with reduced risk of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al (2015) reported that TLR9+2848 had a correlation with systemic lupus erythematosus in a Chinese population. Berenson et al (2015) indicated that TLR9-1237 expression was associated with the development and severity of chronic obstructive pulmonary disease. The studies mentioned above suggest that TLR9 gene polymorphisms are associated with inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Полиморфизм TLR2 (Arg32Gln) ассоцииру-ется с рецидивирующими инфекциями респира-торного тракта, полиморфизм TLR2 (Arg753Gln) сопровождается развитием стафилококкового сепсиса [29,30], полиморфизм TLR9 (T1237C) ассоциирован с повышенным риском развития бронхолегочного аспергиллеза, полиморфизм TLR1 (rs5743551) связывают с нарастанием случаев малярии в азиатской популяции [22]. Кроме того, интересной представляется четкая взаимосвязь наличия полиморфизма TLR9 (T1237C) с рос-том случаев бронхиальной астмы в европейс-кой популяции [16]. Наряду с представленными данными есть исследования, не обнаружившие связи полиморфизма и/или мутаций в TLR4 (Asp299Gly) и TLR2 (Arg753Gln) и увеличением частоты развития инфекций [34,35,36,40].…”
Section: молекулярно-клеточные механизмы активации врожденного и адапunclassified
“…Изучается роль ТПР при пневмониях [13], ХОЗЛ [22], туберкулёзе [3], аутоиммунных болезнях, злокачественных опухолях [34], болезнях почек [17], ТПР обнаружены на эпителиоцитах верхних дыхательных путей [5]. Высказывается мнение, что развитие инфекционных, аутоиммунных, иммунокомплексных болезней возможно только при наличии дефекта ТПР на уровне самих рецепторов, различий сигналов на уровне факторов, регулирующих функции ТПР.…”
unclassified